Krise und Kult Vorderer Orient und Nordafrika von Aurelian bis Justinian - Kreikenbom, Detlev; Mahler, Karl-Uwe; Schollmeyer, Patrick; Weber, Thomas M. (Millennium-Studien / Millennium Studies, 2010)
This volume contains twelve contributions on the urban development of the Near East and North Africa in Late Antiquity. On the one hand the authors consider historical and cultural aspects of the region. A comprehensive section of illustrations of new archaeological material and its interpretation then form the second focus of this volume of papers.